Zwitterionic niobium and tantalum complexes with bidentate aminophenol scaffolds: synthesis, structural characterization and use in the ring opening polymerization of lactides. Issue 54 (17th May 2016) - Roymuhury, Sagnik K.; Chakraborty, Debashis; Ramkumar, Venkatachalam
Abstract : ROP of rac -LA using zwitterionic Nb and Ta complexes resulted in heterotactic enriched PLA. Abstract : The stoichiometric reaction of the aminophenol ligandsL1–L3 with NbCl5 or TaCl5 afforded a series of metal chloride complexes1–6 . These were characterized by 1 H, 13 C NMR, mass spectroscopy and elemental analysis. Complex2 crystallized as ethoxy substituted complex2a upon attempting crystallization from a solvent mixture of chloroform and ethanol. The molecular structure confirms the zwitterionic nature of the complex where the protonated nitrogen atom of the ligand backbone is neutralised by a negative charge on the metal center. Moderate electrostatic hydrogen bonding interactions between the NH + donor moieties and acceptor chlorine atoms stabilise these complexes. The complexes show moderate activities towards the ring opening polymerization (ROP) of lactides ( rac -LA, l -LA) with good control over the polymerization parameters. All the complexes produced heterotactic enriched poly(lactic acid) (PLA). Low molecular weight oligomers prepared and analysed by MALDI-TOF mass and 1 H NMR spectroscopy revealed that the ligand initiates the ROP. The complexes were optimized at the B3LYP/LANL2DZ level and the frontier orbitals were studied in order to calculate the trend in reactivity order theoretically.